Catalytic Conversion of Alcohols into Carboxylic Acid Salts in Water: Scope, Recycling, and Mechanistic Insights. Issue 12 (26th April 2016) - Zhang, Lei; Nguyen, Duc Hanh; Raffa, Guillaume; Trivelli, Xavier; Capet, Frédéric; Desset, Simon; Paul, Sébastien; Dumeignil, Franck; Gauvin, Régis M.
Abstract: The catalytic conversion of alcohols into carboxylic acid salts in water was performed in the presence of ruthenium complexes supported by aliphatic PNP pincer ligands preformed or formed in situ. High activity toward a wide substrate scope was achieved with turnover number values of up to 4000. The air‐stable catalytic system can be recycled by using toluene as a catalyst‐immobilizing phase; the activity is maintained after five consecutive runs. Finally, mechanistic studies allowed some fundamental aspects related to water activation to be unveiled and to the mechanism postulated. Abstract : High yields in a pinch : The catalytic conversion of alcohols into carboxylic acid salts in water occurs in the presence of aliphatic PNP pincer ruthenium complexes. High activity is achieved over a wide substrate scope and the catalyst can be successfully recycled over five consecutive runs. Mechanistic studies allow some fundamental aspects related to water activation to be unveiled and the mechanism postulated.